ISLAMIC PHILOSOPHY FROM ITS ORIGIN TO THE PRESENT - Inayahtulfatiha Inayahtulfatiha; Yusuf Hanafi (Adisam Publisher, 2025)
Philosophy in the Islamic World by Peter Adamson provides a thorough exploration of the development of philosophy within the Islamic tradition, focusing on contributions from Muslim, Jewish, and Christian thinkers. It begins with the formative period, highlighting the translation of Greek philosophical texts into Arabic and their integration into Islamic thought by early philosophers such as Al-Kindi and Al-Farabi. Key themes include theology, metaphysics, logic, and ethics, alongside early schools of thought like the Muʿtazilites and Ashʿarites. The book then examines the Golden Age of Andalusia, featuring influential figures like Ibn Rushd (Averroes), Ibn Tufayl, and Maimonides. Later sections cover the evolution of philosophy in the Eastern Islamic world, including thinkers like Suhrawardi and Mulla Sadra, and the influence of Islamic thought on European philosophy, especially during the Renaissance.